Supply control and product differentiation effects of European protected designations of origin cheeses - Sanchez, Deborah S. (Kansas State University, 2008)
The purpose of this research was to analyze the impact of supply control variables such as market share; DO/PGI cheese hedonic quality attributes such as country of origin, type of milk, and age; and the price of a substitute artesian or farmstead cheese on the price of imported cheeses. The literature review found that the EU has been a leader in developing a process for verifying foods produced in a local geographic area. It also revealed that the ability to control supply of a differentiated product transferred consumer surplus to producer surplus. The economic theory suggests that PDO/PGI certification results in the ability of the group of producers and / or processor to control supply by effectively causing a vertical kink in the supply curve and sufficiently differentiated products have a relatively inelastic demand curve. Data was collected on 83 PDO cheeses manufactured in the EU and sold in the US. This data included market share defined as the total tons of that PDO cheese produced in that geographic region divided by the total hectares of land. Hedonic variables characterize the PDO cheeses based on aging time, type of input and country of production. The price of a competing artisan cheese similar to the PDO cheese was identified. All of these variables were used in an ordinary least squares regression model to explain the variation in the price of the imported cheese. The regression results founded that market share, country of origin (Italy and Spain), and the price of a substitute were significant in explaining the variability in imported PDO cheese prices. Market share had a greater magnitude of change suggesting that, at the margin, a small change in supply can cause a larger change in supply which was not surprising given an inelastic demand curve and a fixed supply curve. Substitutes were actually complements which at first glance appears surprising. Finally, as one might suspect, a cheese that is more mature, like wine, has a greater value.
Keywords: Protected Designation of Origin (PDO); Protected Geographical Indication (PGI); Supply Control; Product Differentiation; Economics, Agricultural (0503)